Education mobility as one of the grand strategies for higher education institutions’ sustainability in 2020s: An academic perspective - Mohd Ali, Hairuddin (The International Institute of Knowledge Management (TIIKM), 2017)
Global Prominence (eighth shift), comprising internationalization and education mobility, is considered as one of the supreme key result areas in Malaysian Education Blueprint 2015-2025 endeavors. In relation to this, this paper focused and discusses Education Mobility as one of the grand strategies for higher education institutions’ sustainability in 2020s from an academic perspective. The discussion starts with the introduction of several education management related theories such as educational strategic management theories, education internationalization theories, education mobility theories and higher education institutions sustainability theories. Next, the paper introduces and discusses the application of those theories in International Islamic University Malaysia (IIUM) long term strategic planning. The paper ends with suggestions and recommendations for IIUM’s strategic planning effective implementation.